Determinant Aspects of Students to Become Entrepreneurs During the Second Wave of Covid-19 - Sidharta, Iwan; Riadi, Farid; Rahman, Robbi Saepul; Ramadhani, Gita Indah; Hidayahtullah, Annaba Raffal (Jurnal Ilmiah Peuradeun, 2023)
Studying successful entrepreneurs is an exciting focus for policymakers, professionals, and academics. It presents different research results so that researchers fill the gap by using student respondents to examine the essential aspects that can drive the desire to become entrepreneurs. The researcher used a cross-sectional approach with student respondents who had attended entrepreneurship courses to discover this aspect. The number of respondents who filled out a structured questionnaire using the Google form was 129 students—the data analysis technique used the Partial Least Square structural equation model. The study results showed that 9 (nine) essential aspects could increase students' desire to become entrepreneurs. This research only used student respondents to examine essential aspects that could encourage the desire to become entrepreneurs. The cross-sectional approach was also tested simultaneously during the second wave of Covid-19. The research results have implications for developing essential aspects for students to become entrepreneurs.